(untitled) (University Arena, 2025)
The paper reviews different types of tennis courts and how those can influence the playing style of the game. In the first section of the text, the author classifies and describes the differences between tennis courts. The most important difference is made by the surface; there are four types of surfaces, so there are four types of courts. Also, differences are made by the dimensions or by the space where the court is placed (indoor or outdoor). This text reviews each type. Additionally, the text explores how each type influence the playing style of the game according to the equipment players are using. The author focuses on direct observation of matches played on each and every type of courts. The paper seek to answer the question: Which are advantages and disadvantages of playing tennis on different types of courts? The author finds out that the most used type is the hart court, especially in U.S.A., even if the grass court is the fastest type of courts. It is hopped this study will inform people that are not athletes about differences between tennis courts in case of playing this sport as a hobby.